Nerve regeneration using decellularized tissues: challenges and opportunities - Mahdian, Maryam; Tabatabai, Tayebeh Sadat; Abpeikar, Zahra; Rezakhani, Leila; Khazaei, Mozafar (Frontiers in Neuroscience, 2023)
In tissue engineering, the decellularization of organs and tissues as a biological scaffold plays a critical role in the repair of neurodegenerative diseases. Various protocols for cell removal can distinguish the effects of treatment ability, tissue structure, and extracellular matrix (ECM) ability. Despite considerable progress in nerve regeneration and functional recovery, the slow regeneration and recovery potential of the central nervous system (CNS) remains a challenge . The success of neural tissue engineering is primarily influenced by composition, microstructure, and mechanical properties. The primary objective of restorative techniques is to guide existing axons properly toward the distal end of the damaged nerve and the target organs. However, due to the limitations of nerve autografts, researchers are seeking alternative methods with high therapeutic efficiency and without the limitations of autograft transplantation.Decellularization scaffolds, due to their lack of immunogenicity and the preservation of essential factors in the ECM and high angiogenic ability, provide a suitable three-dimensional (3D) substrate for the adhesion and growth of axons being repaired towards the target organs.This study focuses on mentioning the types of scaffolds used in nerve regeneration, and the methods of tissue decellularization, and specifically explores the use of decellularized nerve tissues (DNT) for nerve transplantation.